An Investigation the Competence of Preservice Teachers of Economics in the Industrial Revolution Era: A Literature Review - Muhammad Bukhori Dalimunthe; Suranto Suranto (AL-ISHLAH: Jurnal Pendidikan, 2022)
In the 21st Century, advances in information and technology have spurred open access to economic learning for preservice teachers. Reinventing competencies needs to be done to keep pace with the advancement of knowledge and technology in the industrial revolution era. This paper aims to investigate the competence of preservice teachers of economics in the industrial revolution era. The literature review is used to find the challenges faced and the competencies needed by prospective economics teachers. Various relevant and credible literature (Science Direct, Taylor Francis, Emerald) for two decades have been fast reviewed and comprehensively to show the phases, levels, knowledge, competencies, and cognitive-noncognitive domains. The review findings reveal the challenges that preservice teachers of economics face as a provision for mastering competencies as teachers in the industrial revolution era. Next, a synthesis of the competency reviews is needed for preservice teachers of economics to present relevant and credible studies. Finally, this paper has implications for competencies that need to be prepared or reinvented through actions and policies that lead to professional economics teachers.